Pengaruh model pembelajaran kooperatif tipe STAD berbantuan media Articulate Storyline terhadap kemampuan pemecahan masalah matematis siswa SMP - Danisa Berlianta Sembiring (Papanda Publisher, 2026)
This study aims to describe the effect of the STAD cooperative learning model, supported by Articulate Storyline, on the mathematical problem-solving skills of junior high school students. The method used was a quasi-experiment employing a non-equivalent control group design. The population for this study comprised all Year 7 pupils at SMP Negeri 1 Pancur Batu. The sample consisted of Class VII-3, comprising 33 students, as the experimental class taught using the STAD model supported by Articulate Storyline, and Class VII-1, comprising 33 students, as the control class taught using the direct instruction model. Before hypothesis testing was conducted, the data were first tested for normality and homogeneity. Hypothesis testing used the Independent Sample T-Test. The results of the analysis showed that the significance value was <0.001, which is below the significance level of 0.05; therefore, H₀ was rejected and H₁ accepted. The calculation of Cohen’s d showed an effect size of 0.990, which falls into the large category. Based on these findings, it can be concluded that the STAD learning model supported by Articulate Storyline has a significant effect on students’ mathematical problem-solving skills. Furthermore, this study indicates that the STAD learning model supported by Articulate Storyline not only exerts a significant influence but also enhances students’ mathematical problem-solving skills. Furthermore, there was an improvement in students’ mathematics learning, with students becoming more active in the learning process and finding it easier to understand the material taught.